A method for preparing refractory and corrosion-resistant castable for nonferrous metal smelting

By preparing a refractory and erosion-resistant castable material containing a variety of refractory materials, the problem of traditional refractory materials being susceptible to erosion during non-ferrous metal smelting is solved, which significantly improves the refractory and corrosion resistance of the castable material, extends the service life and improves the stability of the smelting process and product quality.

CN119775032APending Publication Date: 2025-04-08JIANGSU NUOMING HIGH TEMPERATURE MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411815660.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Traditional refractory materials are susceptible to erosion by molten metals, slag and high-temperature gases during the non-ferrous metal smelting process, resulting in structural damage and shortening of service life.

Method used

A refractory and corrosion-resistant castable material preparation method including brown corundum, MgAl2O4 powder, activated alumina micro powder, aluminum-magnesium spinel cement, ZrO2 micro powder, B4C micro powder, sodium hexametaphosphate, La2O3 micro powder and alumina particles is adopted. This method ensures that the various raw materials are mixed evenly through dry and wet mixing treatment, and improves the bonding force of brown corundum through surface modification treatment.

Benefits of technology

It significantly improves the fire resistance and corrosion resistance of the castable material, extends the service life, and improves the stability of the smelting process and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775032A_ABST
    Figure CN119775032A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of castable preparation, and in particular to a method for preparing a refractory and erosion-resistant castable for non-ferrous metal smelting, comprising: S1, batching, S2, dry mixing, and S3, wet mixing. The invention obtains modified brown corundum by surface modification of brown corundum particles, and the surface modification can improve the bonding force between brown corundum and other raw materials, enhance the effect of the brown corundum in the castable, and further improve the refractory and erosion-resistant performance of the castable. The modified brown corundum is first mixed with cleaned alumina particles and MgAl2O4 powder to obtain pretreated aggregate, and then other micropowders are added in stages for dry mixing. This mixing sequence can make the raw materials gradually and evenly mixed, avoid the uneven mixing phenomenon caused by one-time mixing, improve the quality of the dry mixed material, and then improve the performance of the castable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of castable preparation, and in particular to a method for preparing a refractory and corrosion-resistant castable for non-ferrous metal smelting. Background Art

[0002] In the smelting process of non-ferrous metals, a high temperature environment is usually required to achieve metal extraction, refining and other operations. In these high-temperature smelting processes, the performance of refractory materials is crucial.

[0003] Traditional refractory materials are easily corroded by molten metal, slag and high-temperature gas during the non-ferrous metal smelting process. Taking copper smelting as an example, the slag contains a variety of oxides, which will chemically react with the refractory material, gradually corroding the matrix of the refractory material and causing its structural damage. As the smelting time increases, the thickness of the refractory material continues to decrease, shortening its service life. Frequent replacement of refractory materials may also affect the stability of the smelting process and product quality.

[0004] Although some existing refractory materials can withstand certain high temperatures, they will soften and deform under long-term high temperature. In some high-temperature and strong heat flow smelting areas, such as the hot spots of the melting furnace, ordinary refractory materials cannot effectively resist the impact of high temperatures and are prone to damage, which in turn affects the normal operation of the entire smelting equipment. During the smelting process, refractory materials must be able to withstand high temperatures and chemical erosion. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a method for preparing a refractory and corrosion-resistant castable for non-ferrous metal smelting.

[0006] The technical solution of the present invention is: a method for preparing a refractory and corrosion-resistant castable for non-ferrous metal smelting, comprising the following steps: S1, batching

[0007] According to the mass percentage, 20-30% of brown corundum, 5-10% of MgAl2O4 powder, 5-10% of activated alumina powder, 4-6% of alumina-magnesium spinel cement, 2-4% of ZrO2 powder, 1-3% of B4C powder, 0.1-0.3% of sodium hexametaphosphate, 0.1-0.3% of La2O3 powder, 0.02-0.08% of C6H8O7 and the balance of alumina particles are taken;

[0008] S2. Dry mixing

[0009] S2-1, wash the alumina particles, brown corundum and MgAl2O4 powder prepared in S1 respectively, and then dry them at a temperature of 110-120°C for 2-3h; sieve the La2O3 micropowder, ZrO2 micropowder and B4C micropowder with a mesh size of 200 to remove large particle agglomerates;

[0010] S2-2, performing surface modification treatment on the cleaned brown corundum particles to obtain modified brown corundum; uniformly mixing the modified brown corundum with the cleaned alumina particles and MgAl2O4 powder to obtain pretreated aggregate;

[0011] S2-3, putting the pretreated aggregate described in S2-2 into a planetary mixer for dry mixing, the mixer speed is controlled to be 150-180r / min, and the dry mixing time is 8-10min; then add the sieved La2O3 micropowder, ZrO2 micropowder and B4C micropowder, dry mix at a speed of 150-180r / min for 5-7min, then add activated alumina micropowder, adjust the speed to 120-150r / min, and continue dry mixing for 5-7min to obtain a dry mixture;

[0012] S3, wet mixing

[0013] Aluminum-magnesium spinel cement, sodium hexametaphosphate and C6H8O7 are added to the dry mixture described in S2-2, and water accounting for 8-10% of the mass ratio of the dry mixture is added at the same time, and wet mixing is stirred evenly to obtain a refractory and corrosion-resistant castable.

[0014] Description: Alumina has high refractoriness and good corrosion resistance, and is one of the main aggregate components of castables. Brown corundum has high hardness and good wear resistance, which can enhance the overall strength and anti-scouring ability of castables. Spinel has good chemical stability at high temperatures, which helps to improve the corrosion resistance of castables to non-ferrous metal melts. Washing and drying alumina particles, brown corundum and MgAl2O4 powder can remove impurities on the surface of raw materials, such as dust and soil, to ensure the purity of raw materials and improve the quality of castables. The drying process can make the raw materials reach a suitable moisture content, which is conducive to the subsequent mixing and reaction process. Screening La2O3 micropowder, ZrO2 micropowder and B4C micropowder with 200 mesh can remove large particle agglomerates, so that these micropowders are evenly dispersed in the castable, avoiding local performance differences caused by agglomeration, and ensuring the uniformity of castable performance.

[0015] Furthermore, in terms of mass percentage, the particle sizes of the alumina particles in S1 include: 35-45% of 5-8 mm alumina particles, 15-30% of 8-10 mm alumina particles, and the remainder of 3-5 mm alumina particles.

[0016] Description: Large gaps are formed between large-sized alumina particles, and suitable medium-sized and small-sized alumina particles can fill these gaps, thereby increasing the packing density of the entire castable. The higher packing density makes the castable structure denser after molding, reduces the presence of defects such as pores, and thus improves the strength and corrosion resistance of the castable.

[0017] Furthermore, the particle size of the brown corundum includes 40-50% of 1-3 mm brown corundum and the remainder of 0.5-1 mm brown corundum; the particle size of the MgAl2O4 powder is 0.1-0.5 mm; and the particle size of the activated alumina powder is 10-50 nm.

[0018] Description: The particle size distribution of brown corundum is that the large particle size provides a strong supporting skeleton, and the small particle size fills the voids, thereby increasing the packing density and overall strength and improving the fluidity of the castable; the particle size of MgAl2O4 powder is 0.1-0.5mm, which can not only fill the voids of the aggregate well, but also increase the specific surface area due to the smaller particle size, thereby improving the reaction activity, and is conducive to reacting with other components at high temperature to improve the high temperature performance and corrosion resistance; the particle size of activated alumina micropowder is 10-50nm, which can fill tiny voids and optimize the microstructure. Its high activity can promote sintering, reduce the sintering temperature, and improve the high temperature strength, hardness and corrosion resistance of the castable.

[0019] Furthermore, the surface modification treatment method of the brown corundum particles in S2-2 is: placing the cleaned brown corundum particles in an alkaline degreasing solution, controlling the temperature to 60-70°C, soaking for 35-60 minutes, and then rinsing with deionized water until neutral to obtain degreasing particles; soaking the degreasing particles in an acid washing solution at room temperature for 10-15 minutes, and then taking them out and drying them at 50-70°C to obtain pretreated particles; placing the pretreated particles in a TiC plating solution, the mass ratio of the pretreated particles to the TiC plating solution is 1:9-15, controlling the temperature to 60-70°C, stirring with a magnetic stirrer, and the stirring speed is 200-300r / min , the plating time is 30 to 60 minutes, and TiC plated particles are obtained; the TiC plated particles are rinsed with deionized water for 3 to 5 times, and then immersed in dilute hydrochloric acid with a mass concentration of 0.5 to 2% for 4 to 6 minutes, and then rinsed with deionized water until neutral to obtain activated particles; the activated particles are placed in a Ni plating solution, the mass ratio of the activated particles to the Ni plating solution is 1:9 to 15, the temperature is controlled at 80 to 90° C., stirred with a magnetic stirrer, the stirring speed is 150 to 250 r / min, the plating time is 75 to 95 minutes, and then rinsed with deionized water for 2 to 6 times, and dried at a temperature of 85 to 100° C. for 2 to 3 hours to obtain modified brown corundum.

[0020] Description: Alkaline degreasing and pickling treatment removes oil and impurities on the surface of brown corundum particles to obtain pure pre-treated particles, providing good surface conditions for subsequent plating. Then, plating in TiC plating solution forms a TiC layer on the particle surface. TiC has high hardness, high melting point and good chemical stability, which can improve the wear resistance and corrosion resistance of brown corundum. After activation by dilute hydrochloric acid immersion, plating in Ni plating solution forms a Ni layer, which can further improve the bonding between brown corundum particles and other raw materials and improve the overall structural stability of the castable. This coating can improve the bonding between brown corundum and other raw materials, and at the same time enhance its corrosion resistance, especially when facing the erosion of molten metal at high temperature.

[0021] Furthermore, the degreasing liquid is composed of 20-30% sodium carbonate, 10-15% sodium hydroxide, 1-3% sodium dodecylbenzene sulfonate and the balance sodium phosphate, calculated by mass percentage.

[0022] Description: Sodium carbonate and sodium hydroxide are highly alkaline and can effectively remove grease stains on the surface of brown corundum particles. Sodium hydroxide has a stronger alkalinity and is helpful for saponification reaction to remove oil. Sodium carbonate can act as a buffer to stabilize the alkaline environment. Sodium dodecylbenzene sulfonate is a surfactant that can reduce the surface tension between oil and solution, making it easier to remove oil stains and enhance the oil removal effect. Sodium phosphate can play a role of dispersion and emulsification, making it difficult for impurities generated during the oil removal process to re-attach to the brown corundum particles. The components are matched according to mass percentage to work synergistically, effectively remove oil and ensure the stability of the oil removal effect.

[0023] Furthermore, the pickling solution is composed of 10-15% hydrochloric acid, 2-4% hydrofluoric acid and the balance water, in terms of mass percentage.

[0024] Description: Hydrochloric acid is highly acidic and can effectively dissolve impurities such as metal oxides on the surface of brown corundum particles. Hydrofluoric acid can further remove siliceous impurities that may exist on the surface of brown corundum and improve the purity of brown corundum. Water, as a solvent, can make hydrochloric acid and hydrofluoric acid evenly mixed and fully contact with brown corundum particles, so that the acid in the pickling solution can clean the surface of brown corundum particles more comprehensively, thereby optimizing the surface state of brown corundum and providing a good foundation for subsequent processing procedures.

[0025] Furthermore, the TiC plating solution is composed of 2-5% TiCl4, 5-7% glucose, 3-5% citric acid, 0.2-0.3% sodium borohydride and the balance water, calculated by mass percentage.

[0026] Description: TiCl4 is the source of Ti element, and TiC is formed during the plating process. Glucose can participate in the reaction as a reducing agent, which is conducive to the formation of TiC; citric acid acts as a complexing agent, which can complex with metal ions, control the reaction speed and metal ion concentration during the plating process, and make the plating more uniform. Sodium borohydride is a strong reducing agent that can enhance the efficiency of the reduction reaction and ensure that TiC can be effectively plated on the brown corundum particles. Water is used as a solvent to evenly disperse the components and ensure the stability of the plating solution and the uniformity of the reaction.

[0027] Furthermore, the Ni plating solution is composed of 5-8% NiSO4·6H2O, 2-4% sodium hypophosphite, 2-4% lactic acid, and 0.5-2% propionic acid, calculated by mass percentage.

[0028] Description: NiSO4·6H2O is the main source of Ni ions, forming a Ni layer during the plating process; sodium hypophosphite, as a reducing agent, can reduce Ni ions to Ni elemental plating on the activated particles; lactic acid and propionic acid play a buffering and complexing role, controlling the pH value of the plating solution, stabilizing the Ni ion concentration, and at the same time helping to improve the binding force between the Ni layer and the particles, making the Ni plating process more stable and efficient, and improving the quality of the Ni layer.

[0029] Furthermore, the stirring and wet mixing time in S3 is 12 to 15 minutes, and the stirring speed is controlled to be 80 to 100 r / min.

[0030] Note: Appropriate stirring time can ensure that all kinds of raw materials are fully mixed and uniform, avoiding local uneven components that affect the performance of the castable, and the speed of 8-100r / min can generate appropriate stirring force to mix the raw materials, and will not cause the raw materials to splash or damage the structure of the raw materials due to excessive speed, thereby ensuring the quality of the castable.

[0031] The beneficial effects of the present invention are:

[0032] The present invention selects active alumina powder to promote the densification of the castable during the sintering process and improve its strength; zirconium oxide has good thermal stability and corrosion resistance, and boron carbide has high hardness and good chemical stability, which can enhance the castable's corrosion resistance to non-ferrous metals at high temperatures, and can improve the castable's thermal shock resistance and corrosion resistance; aluminum-magnesium spinel cement can provide good bonding performance to ensure the integrity of the castable during molding and use; sodium hexametaphosphate is used as a dispersant to help improve the fluidity of the castable and make the mixing of various raw materials more uniform; C6H8O7 can adjust the setting time of the castable to facilitate construction operations;

[0033] The modified brown corundum is obtained by surface modification of brown corundum particles. The surface modification can improve the bonding force between brown corundum and other raw materials, enhance its effect in the castable, and further improve the refractory and anti-corrosion properties of the castable. The modified brown corundum is first mixed with the cleaned alumina particles and MgAl2O4 powder to obtain pretreated aggregate, and then other micropowders are added in stages for dry mixing. This mixing sequence can make the raw materials gradually and evenly mixed, avoid the uneven mixing caused by one-time mixing, improve the quality of the dry mix, and then improve the performance of the castable. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is a bar graph of the compressive strength test of samples of Examples 1 to 5, 8, 9 and Comparative Examples 1 to 5 of the present invention;

[0035] Figure 2 It is a bar graph of the line change rate test after burning of samples of Examples 1 to 5, 8, 9 of the present invention and Comparative Examples 1 to 5. DETAILED DESCRIPTION

[0036] In order to further illustrate the method and effect of the present invention, the technical solution of the present invention will be clearly and completely described in combination with experiments.

[0037] Embodiment 1:

[0038] A method for preparing a refractory and corrosion-resistant castable for non-ferrous metal smelting, comprising the following steps:

[0039] S1. Ingredients

[0040] According to the mass percentage, 25% of brown corundum, 7.5% of MgAl2O4 powder, 7.5% of activated alumina powder, 5% of alumina-magnesium spinel cement, 3% of ZrO2 powder, 2% of B4C powder, 0.2% of sodium hexametaphosphate, 0.2% of La2O3 powder, 0.05% of C6H8O7 and the balance of alumina particles are taken;

[0041] The particle sizes of the alumina particles include: 40% of 6-6.5 mm alumina particles, 15-30% of 9-9.5 mm alumina particles and the remainder of 3.5-4.5 mm alumina particles;

[0042] The particle size of the brown corundum includes 45% of 1.5-2.5 mm brown corundum and the rest of 0.7-0.8 mm brown corundum; the particle size of the MgAl2O4 powder is 0.2-0.3 mm; the particle size of the activated alumina powder is 30-40 nm;

[0043] S2. Dry mixing

[0044] S2-1, wash the alumina particles, brown corundum and MgAl2O4 powder prepared in S1 respectively, and then dry them at a temperature of 115°C for 2.5 hours; sieve the La2O3 micropowder, ZrO2 micropowder and B4C micropowder with a mesh size of 200 to remove large particle agglomerates;

[0045] S2-2, put the cleaned brown corundum particles into alkaline degreasing solution, control the temperature to 65 ° C, soak for 47.5 minutes, and then rinse with deionized water until neutral to obtain degreasing particles; soak the degreasing particles in acid solution at room temperature for 12.5 minutes, then take out and dry at 60 ° C to obtain pretreated particles; put the pretreated particles into TiC plating solution, the mass ratio of pretreated particles to TiC plating solution is 1:10-12, control the temperature at 65 ° C, stir with a magnetic stirrer, the stirring speed is 250r / min, and the plating time is 45min, to obtain plated TiC particles; the plated TiC particles were rinsed with deionized water for 4 times, then immersed in dilute hydrochloric acid with a mass concentration of 1.75% for 5min, and then rinsed with deionized water until neutral to obtain activated particles; the activated particles were placed in a Ni plating solution, the mass ratio of the activated particles to the Ni plating solution was 1:12, the temperature was controlled at 85°C, stirred with a magnetic stirrer, the stirring speed was 200r / min, the plating time was 85min, then rinsed with deionized water for 4 times, and dried at a temperature of 97°C for 2.5h to obtain modified brown corundum;

[0046] The degreasing solution is composed of 25% sodium carbonate, 12.5% ​​sodium hydroxide, 2% sodium dodecylbenzene sulfonate and the balance sodium phosphate; the pickling solution is composed of 12.5% ​​hydrochloric acid, 3% hydrofluoric acid and the balance water; the TiC plating solution is composed of 3.5% TiCl4, 6% glucose, 4% C6H8O7, 0.25% sodium borohydride and the balance water; the Ni plating solution is composed of 6.5% NiSO4·6H2O, 3% sodium hypophosphite, 3% lactic acid and 1% propionic acid;

[0047] The modified brown corundum is mixed evenly with the cleaned alumina particles and MgAl2O4 powder to obtain a pretreated aggregate;

[0048] S2-3, the pretreated aggregates described in S2-2 are placed in a planetary mixer for dry mixing, the mixer speed is controlled to 165r / min, and the dry mixing time is 9min; then the sieved La2O3 powder, ZrO2 powder and B4C powder are added, and the mixture is dry mixed at a speed of 165r / min for 6min, and then the activated alumina powder is added, the speed is adjusted to 135r / min, and the dry mixing is continued for 6min to obtain a dry mixture;

[0049] S3, wet mixing

[0050] Aluminum-magnesium spinel cement, sodium hexametaphosphate and C6H8O7 are added to the dry mix described in S2-2, and water accounting for 9% of the dry mix by mass is added at the same time. The mixture is stirred and wet mixed for 13.5 minutes, and the mixer speed is controlled at 90r / min to obtain a refractory and corrosion-resistant castable.

[0051] Example 2: This example is basically the same as Example 1, except that, by mass percentage, 20% brown corundum, 5% MgAl2O4 powder, 5% activated alumina powder, 4% alumina-magnesium spinel cement, 2% ZrO2 powder, 1% B4C powder, 0.1% sodium hexametaphosphate, 0.1% La2O3 powder, 0.02% C6H8O7 and the remainder alumina particles are taken.

[0052] Example 3: This example is basically the same as Example 1, except that, by mass percentage, 30% of brown corundum, 10% of MgAl2O4 powder, 10% of activated alumina powder, 6% of aluminum-magnesium spinel cement, 4% of ZrO2 powder, 3% of B4C powder, 0.3% of sodium hexametaphosphate, 0.3% of La2O3 powder, 0.08% of C6H8O7 and the remainder of alumina particles are taken.

[0053] Example 4: This example is basically the same as Example 1, except that the pretreated aggregate described in S2-2 is put into a planetary mixer for dry mixing, the mixer speed is controlled to 150r / min, and the dry mixing time is 8min; then the sieved La2O3 micropowder, ZrO2 micropowder and B4C micropowder are added, and the mixture is dry mixed at a speed of 150r / min for 5min, and then the activated alumina micropowder is added, the speed is adjusted to 120r / min, and the dry mixing is continued for 5min to obtain a dry mixture.

[0054] Example 5: This example is basically the same as Example 1, except that the pretreated aggregate described in S2-2 is put into a planetary mixer for dry mixing, the mixer speed is controlled to 180r / min, and the dry mixing time is 10min; then the sieved La2O3 micropowder, ZrO2 micropowder and B4C micropowder are added, and the mixture is dry mixed at a speed of 180r / min for 7min, and then the activated alumina micropowder is added, the speed is adjusted to 150r / min, and the dry mixing is continued for 7min to obtain a dry mixture.

[0055] Example 6: This example is basically the same as Example 1, except that the particle size of the alumina particles in S1 includes: 35% of 5-5.5 mm alumina particles, 15-30% of 8-8.5 mm alumina particles and the remainder of 3-3.5 mm alumina particles; the particle size of the brown corundum includes 40% of 1-1.5 mm brown corundum and the remainder of 0.5-0.6 mm brown corundum; the particle size of the MgAl2O4 powder is 0.1-0.2 mm; the particle size of the activated alumina micropowder is 10-20 nm.

[0056] Example 7: This example is basically the same as Example 1, except that the particle size of the alumina particles in S1 includes: 45% of 7-8 mm alumina particles, 30% of 9-10 mm alumina particles and the remainder of 4-5 mm alumina particles; the particle size of the brown corundum includes 50% of 2-3 mm brown corundum and the remainder of 0.8-1 mm brown corundum; the particle size of the MgAl2O4 powder is 0.4-0.5 mm; the particle size of the activated alumina powder is 40-50 nm.

[0057] Example 8: This example is basically the same as Example 1, except that the surface modification treatment method of the brown corundum particles in S2-2 is as follows: the cleaned brown corundum particles are placed in an alkaline degreasing solution, the temperature is controlled at 60-70°C, soaked for 35 minutes, and then rinsed with deionized water until neutral to obtain degreasing particles; the degreasing particles are soaked in an acid washing solution at room temperature for 10 minutes, and then taken out and dried at 50°C to obtain pretreated particles; the pretreated particles are placed in a TiC plating solution, the mass ratio of the pretreated particles to the TiC plating solution is 1:9, the temperature is controlled at 60°C, and a magnetic stirrer is used to stir the particles. Stirring, the stirring speed is 200r / min, the plating time is 30min, and TiC plated particles are obtained; the TiC plated particles are rinsed with deionized water for 3 times, and then immersed in dilute hydrochloric acid with a mass concentration of 0.5% for 4min, and then rinsed with deionized water until neutral to obtain activated particles; the activated particles are placed in a Ni plating solution, the mass ratio of the activated particles to the Ni plating solution is 1:9, the temperature is controlled at 80°C, stirred with a magnetic stirrer, the stirring speed is 150r / min, the plating time is 75min, and then rinsed with deionized water for 2 times, and dried at a temperature of 85°C for 2h to obtain modified brown corundum.

[0058] Example 9: This example is basically the same as Example 1, except that the surface modification treatment method of the brown corundum particles in S2-2 is as follows: the cleaned brown corundum particles are placed in an alkaline degreasing solution, the temperature is controlled at 70°C, soaked for 60 minutes, and then rinsed with deionized water until neutral to obtain degreasing particles; the degreasing particles are soaked in an acid wash solution at room temperature for 15 minutes, then taken out and dried at 70°C to obtain pretreated particles; the pretreated particles are placed in a TiC plating solution, the mass ratio of the pretreated particles to the TiC plating solution is 1:15, the temperature is controlled at 70°C, and stirred with a magnetic stirrer. The plated TiC particles were rinsed with deionized water for 5 times, then immersed in dilute hydrochloric acid with a mass concentration of 2% for 6 minutes, and then rinsed with deionized water until neutral to obtain activated particles; the activated particles were placed in a Ni plating solution with a mass ratio of activated particles to Ni plating solution of 1:15, the temperature was controlled at 90°C, stirred with a magnetic stirrer at a stirring speed of 250r / min, the plating time was 95min, then rinsed with deionized water for 6 times, and dried at 100°C for 3h to obtain modified brown corundum.

[0059] Example 10: This example is basically the same as Example 1, except that the TiC plating solution consists of 2% TiCl4, 5% glucose, 3% C6H8O7, 0.2% sodium borohydride and the balance water.

[0060] Example 11: This example is basically the same as Example 1, except that the TiC plating solution consists of 5% TiCl4, 7% glucose, 5% C6H8O7, 0.3% sodium borohydride and the remainder water.

[0061] Example 12: This example is basically the same as Example 1, except that the Ni plating solution consists of 5% NiSO4·6H2O, 2% sodium hypophosphite, 2% lactic acid, and 0.5% propionic acid.

[0062] Example 13: This example is basically the same as Example 1, except that the Ni plating solution consists of 8% NiSO4·6H2O, 4% sodium hypophosphite, 4% lactic acid, and 2% propionic acid.

[0063] Control Example 1: Taking Example 1 as a reference, take, by mass percentage, 15% of brown corundum, 4% of MgAl2O4 powder, 4% of activated alumina powder, 2% of alumina-magnesium spinel cement, 1% of ZrO2 powder, 0.5% of B4C powder, 0.05% of sodium hexametaphosphate, 0.05% of La2O3 powder, 0.01% of C6H8O7 and the remainder of alumina particles.

[0064] Control Example 2: Taking Example 1 as a reference, take, by mass percentage, 35% of brown corundum, 15% of MgAl2O4 powder, 12% of activated alumina powder, 8% of alumina-magnesium spinel cement, 6% of ZrO2 powder, 4% of B4C powder, 0.5% of sodium hexametaphosphate, 0.5% of La2O3 powder, 0.1% of C6H8O7 and the remainder of alumina particles.

[0065] Comparative Example 3: In S2, the brown corundum particles were not surface modified.

[0066] Comparative Example 4: With reference to Example 1, the surface modification treatment method of the brown corundum particles in S2-2 is as follows: the cleaned brown corundum particles are placed in an alkaline degreasing solution, the temperature is controlled at 50°C, soaked for 25 minutes, and then rinsed with deionized water until neutral to obtain degreasing particles; the degreasing particles are soaked in an acid wash solution at room temperature for 8 minutes, and then taken out and dried at 40°C to obtain pretreated particles; the pretreated particles are placed in a TiC plating solution, the mass ratio of the pretreated particles to the TiC plating solution is 1:8, the temperature is controlled at 50°C, and stirred with a magnetic stirrer at a stirring speed of 150r / min, the plating time is 25min, and TiC plated particles are obtained; the TiC plated particles are rinsed with deionized water for 3 to 5 times, and then immersed in dilute hydrochloric acid with a mass concentration of 0.3% for 3min, and then rinsed with deionized water until neutral to obtain activated particles; the activated particles are placed in a Ni plating solution, the mass ratio of the activated particles to the Ni plating solution is 1:8, the temperature is controlled at 70°C, stirred with a magnetic stirrer, the stirring speed is 200r / min, the plating time is 70min, and then rinsed with deionized water once, and dried at a temperature of 85 to 100°C for 1.5h to obtain modified brown corundum.

[0067] Comparative Example 5: With reference to Example 1, the surface modification treatment method of the brown corundum particles in S2-2 is as follows: the cleaned brown corundum particles are placed in an alkaline degreasing solution, the temperature is controlled at 75°C, soaked for 65 minutes, and then rinsed with deionized water until neutral to obtain degreasing particles; the degreasing particles are soaked in an acid wash solution at room temperature for 20 minutes, then taken out and dried at 75°C to obtain pretreated particles; the pretreated particles are placed in a TiC plating solution, the mass ratio of the pretreated particles to the TiC plating solution is 1:16, the temperature is controlled at 75°C, and stirred with a magnetic stirrer at a stirring speed of 35 0r / min, the plating time is 65min, and TiC plated particles are obtained; the TiC plated particles are rinsed with deionized water for 6 times, and then immersed in dilute hydrochloric acid with a mass concentration of 2.5% for 7min, and then rinsed with deionized water until neutral to obtain activated particles; the activated particles are placed in a Ni plating solution, the mass ratio of the activated particles to the Ni plating solution is 1:16, the temperature is controlled at 95°C, stirred with a magnetic stirrer, the stirring speed is 280r / min, the plating time is 100min, and then rinsed with deionized water for 7 times, and dried at a temperature of 125°C for 3.5h to obtain modified brown corundum.

[0068] In order to explore the performance of castables in some embodiments and control examples, the main materials were determined according to the experimental formula and samples were obtained for testing. They were dried at 110°C for 24 hours and kept at 1300°C for 3 hours. According to GB / T3001-2007 and GB / T5988-2007, the compressive strength and post-firing linear change rate of the castables were tested respectively. The results are as follows: Figure 1 , 2 The specific research is as follows:

[0069] 1. Explore the influence of batching parameters on castable performance:

[0070] like Figure 1 , 2 As shown, by comparing Examples 1 to 3, it can be seen that: it can be seen that Example 1 has high compressive strength, small line change after firing, and better comprehensive performance; changing the raw material ratio parameters will have a certain impact on the prepared castable sample, and Example 3 has the worst compressive strength; compared with Control Examples 1 and 2, it can be seen that the performance of the samples prepared using process parameters beyond the scope of this method is significantly reduced, and the pressure and fire resistance of Control Example 2 are lower than those of Control Example 1, and the comprehensive performance of Control Example 1 is much lower than that of Example 3, among which the castable prepared using the process parameter values ​​of Example 1 has the best comprehensive performance.

[0071] 2. Investigate the influence of dry mixing process parameters on castable performance:

[0072] like Figure 1 , 2As shown, by comparing Examples 1, 4, and 5, it can be seen that: it can be seen that the comprehensive performance of Example 1 is the best; the compressive strength of Example 5 is better than that of Example 4, and the high temperature resistance of Example 4 is slightly higher than that of Example 5. Changing the process parameters of the dry mixing treatment will have a certain effect on the performance of the castable sample, among which the castable prepared by the process parameter value closer to Example 1 has the best comprehensive performance.

[0073] 3. Explore the influence of brown corundum modification process on castable properties:

[0074] like Figure 1 , 2 As shown, by comparing Examples 1, 8, and 9, it can be seen that the castable prepared according to the method of Example 1 has the best comprehensive performance, and the comprehensive performance of Example 8 is better than that of Example 9. It can be seen that the process parameters of the modified treatment can have a certain influence on the performance of the castable, and controlling the appropriate ratio can improve its compressive strength and refractory performance.

[0075] From the comparison between Example 1 and Control Examples 3 to 5, it can be seen that the compressive strength of Example 9 is significantly better than that of Control Example 3, the compressive strength and the line change rate after burning of Control Examples 4 and 5 are significantly better than those of Control Example 3, the compressive strength and the line change rate after burning of Control Example 4 are better than those of Control Example 5, but are far lower than those of Example 1. The modification operation and the change of its process parameter range have a more obvious effect on the effect of the castable, and the castable prepared within the parameter range of this scheme has better comprehensive performance.

Claims

1. A method for preparing a refractory and corrosion-resistant castable for non-ferrous metal smelting, characterized in that: The following steps are involved: S1. Ingredients According to the mass percentage, 20-30% of brown corundum, 5-10% of MgAl2O4 powder, 5-10% of activated alumina powder, 4-6% of alumina-magnesium spinel cement, 2-4% of ZrO2 powder, 1-3% of B4C powder, 0.1-0.3% of sodium hexametaphosphate, 0.1-0.3% of La2O3 powder, 0.02-0.08% of C6H8O7 and the balance of alumina particles are taken; S2. Dry mixing S2-1, wash the alumina particles, brown corundum and MgAl2O4 powder prepared in S1 respectively, and then dry them at a temperature of 110-120°C for 2-3h; sieve the La2O3 micropowder, ZrO2 micropowder and B4C micropowder with a mesh size of 200 to remove large particle agglomerates; S2-2, performing surface modification treatment on the cleaned brown corundum particles to obtain modified brown corundum; uniformly mixing the modified brown corundum with the cleaned alumina particles and MgAl2O4 powder to obtain pretreated aggregate; S2-3, putting the pretreated aggregate described in S2-2 into a planetary mixer for dry mixing, the mixer speed is controlled to be 150-180r / min, and the dry mixing time is 8-10min; then add the sieved La2O3 micropowder, ZrO2 micropowder and B4C micropowder, dry mix at a speed of 150-180r / min for 5-7min, then add activated alumina micropowder, adjust the speed to 120-150r / min, and continue dry mixing for 5-7min to obtain a dry mixture; S3, wet mixing Aluminum-magnesium spinel cement, sodium hexametaphosphate and C6H8O7 are added to the dry mixture described in S2-2, and water accounting for 8-10% of the mass ratio of the dry mixture is added at the same time, and wet mixing is stirred evenly to obtain a refractory and corrosion-resistant castable.

2. The method for preparing a refractory and corrosion-resistant castable for non-ferrous metal smelting according to claim 1, characterized in that: In terms of mass percentage, the particle sizes of the alumina particles in S1 include: 35-45% of 5-8 mm alumina particles, 15-30% of 8-10 mm alumina particles, and the remainder of 3-5 mm alumina particles.

3. The method for preparing a refractory and corrosion-resistant castable for non-ferrous metal smelting according to claim 1, characterized in that: The particle size of the brown corundum in S1 includes 40-50% of 1-3 mm brown corundum and the remainder of 0.5-1 mm brown corundum; the particle size of the MgAl2O4 powder is 0.1-0.5 mm; and the particle size of the activated alumina powder is 10-50 nm.

4. The method for preparing a refractory and corrosion-resistant castable for non-ferrous metal smelting according to claim 1, characterized in that: The surface modification treatment method of the brown corundum particles in S2-2 is as follows: the cleaned brown corundum particles are placed in an alkaline degreasing solution, the temperature is controlled at 60-70°C, soaked for 35-60 minutes, and then rinsed with deionized water until neutral to obtain degreasing particles; the degreasing particles are soaked in an acid wash solution at room temperature for 10-15 minutes, and then taken out and dried at 50-70°C to obtain pretreated particles; the pretreated particles are placed in a TiC plating solution, the mass ratio of the pretreated particles to the TiC plating solution is 1:9-15, the temperature is controlled at 60-70°C, stirred with a magnetic stirrer at a stirring speed of 200-300 r / min, and plating is performed. The time is 30 to 60 minutes to obtain plated TiC particles; the plated TiC particles are rinsed with deionized water for 3 to 5 times, then immersed in dilute hydrochloric acid with a mass concentration of 0.5 to 2% for 4 to 6 minutes, and then rinsed with deionized water until neutral to obtain activated particles; the activated particles are placed in a Ni plating solution, the mass ratio of the activated particles to the Ni plating solution is 1:9 to 15, the temperature is controlled at 80 to 90°C, stirred with a magnetic stirrer, the stirring speed is 150 to 250 r / min, the plating time is 75 to 95 minutes, then rinsed with deionized water for 2 to 6 times, and dried at a temperature of 85 to 100°C for 2 to 3 hours to obtain modified brown corundum.

5. The method for preparing a refractory and corrosion-resistant castable for non-ferrous metal smelting according to claim 4, characterized in that: Calculated by mass percentage, the degreasing liquid consists of 20-30% of sodium carbonate, 10-15% of sodium hydroxide, 1-3% of sodium dodecylbenzene sulfonate and the balance of sodium phosphate.

6. The method for preparing a refractory and corrosion-resistant castable for non-ferrous metal smelting according to claim 4, characterized in that: In terms of mass percentage, the pickling solution consists of 10-15% hydrochloric acid, 2-4% hydrofluoric acid and the balance of water.

7. The method for preparing a refractory and corrosion-resistant castable for non-ferrous metal smelting according to claim 4, characterized in that: Calculated by mass percentage, the TiC plating solution consists of 2-5% TiCl4, 5-7% glucose, 3-5% C6H8O7, 0.2-0.3% sodium borohydride and the balance water.

8. The method for preparing a refractory and corrosion-resistant castable for non-ferrous metal smelting according to claim 4, characterized in that: Calculated by mass percentage, the Ni plating solution consists of 5-8% NiSO4·6H2O, 2-4% sodium hypophosphite, 2-4% lactic acid and 0.5-2% propionic acid.

9. The method for preparing a refractory and corrosion-resistant castable for non-ferrous metal smelting according to claim 1, characterized in that: The stirring and wet mixing time in S3 is 12 to 15 minutes, and the stirring speed is controlled to be 80 to 100 r / min.